Birth Weight and Risk Factors for Atherosclerosis: A Retrospective Cohort Study in Japanese Workers - Azegami, Tatsuhiko; Murai-Takeda, Ayano; Sato, Yasunori; Kanda, Takeshi; Itoh, Hiroshi; Mori, Masaaki (Cardiology and Cardiovascular Medicine, 2020)
Background and aims: Low birth weight is associated not only with poor birth outcome but also chronic health conditions such as hypertension in later life. B-type natriuretic peptide (BNP) is a prognostic factor of cardiovascular events in the general population. However, the association between birth weight and BNP remains unclear. Here, we examined the relationships among birth weight and risk factors for atherosclerosis, including BNP, in Japanese workers. Methods: A total of 1109 (517 male, 592 female; age 40–70 years) participants in an annual medical checkup were enrolled. Subjects were divided into three groups according to birth weight, and the associations between their birth weight and risk factors for atherosclerosis were examined by statistical analysis. Results: Jonckheere–Terpstra trend test according to birth weight category revealed that although birth weight was not correlated with BNP level, it was inversely associated with HbA1c in men and with diastolic blood pressure in women. Correlation coefficient tests for both categorical and continuous birth weight data confirmed the trend test findings. Multiple regression analysis indicated that birth weight was an explanatory factor for HbA1c in men and for diastolic blood pressure in women. Conclusions: Although no significant association was observed between birth weight and BNP, inverse associations between birth weight and HbA1c in men and diastolic blood pressure in women were found. These findings suggest that birth weight may partially predict future risk of cardiovascular events.